Proyek Hijau Tatakura: Sinergi Antara Edukasi Lingkungan dan Implementasi Kurikulum Berkelanjutan - Mellisa Mellisa; Ibnu Hajar; Yeyendra Yeyendra; Cyintia Kumalasari; Yandri Waltriandi; Riadatil Fitri; Dea Putri Ramadhani (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to integrate a green project through the production of Tatakura (Takakura Home Method) compost into the school curriculum as a form of environmental education and sustainable learning. The program was implemented at SMPN 10 Pekanbaru and involved 25 students and four science teachers through stages of socialization, hands-on compost production, mentoring, and the application of the compost to school plants. The activity employed a Participatory Action Research approach that emphasized the active involvement of both teachers and students. Evaluation was conducted using learning achievement tests, environmental awareness attitude questionnaires, and partner satisfaction surveys. The data were analyzed descriptively by comparing mean scores and achievement percentages. The results indicate an improvement in students’ average scores from 84.8 to 87.2, an environmental awareness level of 88%, and partner satisfaction rates of 100% among teachers and 97% among students. These findings demonstrate that the program is effective in supporting the integration of environmental education and the implementation of Education for Sustainable Development.